Real-time quantitative PCR method for assessing wheat cultivars for resistance to Zymoseptoria tritici - Adhikari, Tika B.; Balaji, Boovaraghan; Goodwin, Stephen B. (Frontiers in Plant Science, 2025)
IntroductionSeptoria tritici blotch, caused by Zymoseptoria tritici (formerly Mycosphaerella graminicola), is an economically significant disease of wheat (Triticum aestivum) worldwide. However, there is little understanding of the growth dynamics of the causal fungus during the 14- to 18-day latent period between penetration and symptom expression, making it challenging to develop wheat cultivars resistant to Z. tritici. Furthermore, environmental factors and variations in disease-scoring systems among evaluators add to the complexity. To address these issues and quantify fungal growth during the initial stages of infection, we developed a real-time quantitative polymerase chain reaction (qPCR) method to monitor the T. aestivum - Z. tritici pathosystem.MethodsThe assay used specific primers designed from ß-tubulin gene sequences of Z. tritici to quantify fungal DNA in susceptible and resistant wheat cultivars and segregating recombinant-inbred lines (RILs) that were inoculated at seedling and adult-plant stages with low or high concentrations of inoculum. The real-time PCR method was compared with visual disease assessment for 0 to 27 days after inoculation (DAI).ResultsThe results showed that fungal DNA increased more quickly in two susceptible cultivars than in resistant cultivars with the Stb4 or Stb8 genes for resistance. In the susceptible cultivars, the amount of fungal DNA remained low until symptoms became visible at around 18 DAI. Disease severity and fungal DNA in the two resistant cultivars were less than in either susceptible cultivar, starting at 12 DAI. The differences in fungal DNA between resistant and susceptible cultivars were more significant in adult plant tests that used a higher concentration of inoculum.DiscussionThe data analyses showed that the fungus was not eliminated during resistant interactions but could persist throughout the 27 days. Our results suggest that the real-time PCR method can distinguish between resistant and susceptible cultivars starting at 12 DAI and can be used to evaluate early-stage breeding materials for both quantitative and qualitative resistance to Z. tritici.